PENGARUH SUPERVISI AKADEMIK, SARANA PRASARANA, DAN KOMPETENSI PROFESIONAL GURU TERHADAP MUTU LULUSAN SD NEGERI DI KECAMATAN TODANAN KABUPATEN BLORA - WARTIIN, WARTIIN; KUSUMANINGSIH, WIDYA; SOEDJONO, SOEDJONO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This research aims to examine and analyze: (1) the influence of academic supervision on the quality of graduates, (2) the influence of infrastructure on the quality of graduates, (3) the professional competence of teachers on the quality of graduates, and (4) the influence of academic supervision, infrastructure and competency teacher professionalism simultaneously affects the quality of graduates. Based on the research results, it can be concluded as follows: (1) Academic supervision has a positive and significant effect on improving the quality of graduates. This result is based on the positive t test results, it is proven that the calculated t1 result is 6.881> t table 1.652, (2) Infrastructure has a positive effect on improving the quality of graduates. This result is based on the positive t test results, it is proven that the calculated t2 result is 4.034 < t table 1.652, (3) Teacher Professional Competence has a positive effect on improving the quality of graduates. This result is based on the positive t test results, it is proven that the calculated t3 result is 4.289 < t table 1.652, (4) The influence of Academic Supervision, Infrastructure and Teacher Professional Competence simultaneously has a positive and significant effect on the Quality of Graduates. This is based on positive F test results, it is proven that the value of Fcount > Ftable (285,590 > 3,040). ABSTRAKPenelitian ini bertujuan untuk menguji dan menganalisis: (1) pengaruh supervise akademik terhadap mutu lulusan, (2) pengaruh sarana prasarana terhadap mutu lulusan, (3) kompetensi profesional guru terhadap mutu lulusan, dan (4) pengaruh supervise akademik, sarana prasarana dan kompetensi profesional guru secara simultan terhadap mutu lulusan. Berdasarkan hasil penelitian dapat disimpulkan sebagai berikut: (1) Supervisi akademik berpengaruh positif dan signifikan terhadap peningkatan mutu lulusan. Hasil ini berdasarkan hasil uji t positif, terbukti hasil t1 hitung 6,881> t tabel 1.652, (2) Sarana Prasarana berpengaruh positif terhadap peningkatan mutu lulusan. Hasil ini berdasarkan hasil uji t positif, terbukti hasil t2 hitung 4,034 < t tabel 1,652, (3) Kompetensi Profesional Guru berpengaruh positif terhadap peningkatan mutu lulusan. Hasil ini berdasarkan hasil uji t positif, terbukti hasil t3 hitung 4,289 < t tabel 1,652, (4) Pengaruh Supervisi Akademik, Sarana Prasarana dan Kompetensi Profesional Guru secara simultan berpengaruh positif dan signifikan terhadap Mutu Lulusan. Hal ini berdasar hasil Uji F positif, terbukti nilai Fhitung > Ftabel (285,590 > 3,040).